2004
DOI: 10.2134/agronj2004.0601
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Dilution Curves and Nitrogen Use Efficiency During Winter–Spring Growth of Annual Ryegrass

Abstract: processes (Touraine et al., 1994), a high N requirement during late winter and early spring has been observed For some species, mathematical models have been developed to for annual ryegrass (Salette et al., 1984). However, since describe tissue N dilution during crop growth and to estimate the the rate of soil N mineralization varies throughout the plant N status applying the N nutrition index (NNI), the ratio betweenyear, mainly in response to soil temperature and water the actual tissue N concentration and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
45
0
8

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(62 citation statements)
references
References 30 publications
9
45
0
8
Order By: Relevance
“…Así, se puede sugerir que la calidad del pasto, respecto a su contenido de PC disminuye en la época de lluvias lo cual puede ser asociado con el crecimiento rápido del pasto en esta época. Greenwood et al (1990) y Marino et al (2004) entre otros han denominado a dicho fenómeno "dilución del nitrógeno (N)", o dilución de la proteína (N x 6.25).…”
Section: Resultados Y Discusión Composición Nutrimental De Los Forrajunclassified
See 1 more Smart Citation
“…Así, se puede sugerir que la calidad del pasto, respecto a su contenido de PC disminuye en la época de lluvias lo cual puede ser asociado con el crecimiento rápido del pasto en esta época. Greenwood et al (1990) y Marino et al (2004) entre otros han denominado a dicho fenómeno "dilución del nitrógeno (N)", o dilución de la proteína (N x 6.25).…”
Section: Resultados Y Discusión Composición Nutrimental De Los Forrajunclassified
“…Thus, it can be suggested that the quality of grass, about their PC content decreases in the rainy season which can be associated with the rapid growth of the grass at this time. Greenwood et al (1990) and Marino et al (2004) among others have called this phenomenon "dilution of nitrogen (N)", or dilution of the protein (N x 6.25).…”
Section: Resultados Y Discusión Composición Nutrimental De Los Forrajmentioning
confidence: 99%
“…The critical N dilution curve represents the upper limit of plant N concentration with which maximum biomass yield can be achieved during growth. Both critical and general N dilution curves have been empirically determined for many crops (Flénet et al 2006;Gislum and Boelt 2009;Herrmann and Taube 2004;Lemaire et al 2008;Marino et al 2004). Values below the critical N dilution curve represent sub-optimal nutrient conditions and values above represent supra-optimal conditions (Gastal and Lemaire 2002).…”
Section: Introductionmentioning
confidence: 99%
“…This is supported by the fact that maximum yields with the use of urea are expected to be lower than with CAN (Van Burg et al, 1982). The relatively lower DMY levels encountered in the grass fertilised with urea did not lead to increased N content in harvested plant material (N PLANT ); conversely, CAN or nBTPT-U did not show a dilution effect (Marino et al, 2004). …”
Section: Comparison Of the Three N Sourcesmentioning
confidence: 89%